Urgensi Pendidikan Karakter dalam Pengembangan Mental Peserta Didik - Siti Aisyah (Tafhim Al-'Ilmi, 2022)
Abstract The formation of personality cannot be separated from how we built the character of human resources. The formation of the character of human resources is vital and there is no other choice to create a new Indonesia, namely an Indonesia that can face regional and global challenges. The regional and global challenge in question is how our young generation not only has cognitive abilities, but also touches affective and moral aspects. Character education really needs to be instilled as early as possible to anticipate problems in the future which are increasingly complex, such as children's low attention and concern for the surrounding environment, irresponsibility, low self-confidence, and others. Keywords: Pendidikan Karakter, Pengembangan Mental